“Letters to the Neighbors” by Conservative Publicist M. O. Menshikov as a Source on the History of Russian Everyday Life at the Beginning of 20th Century - M. N. Nachapkin (Научный диалог)
“Letters to neighbors” by M. O. Menshikov are analyzed by the author of the article as a historical and literary source. It is reported that in the first volume of “Letters to the Neighbors” the most important contradictions and problems of Russian life were considered, the unresolvedness of which led to revolutions of the beginning of the 20th century. It is noted that the journalism of M. O. Menshikov had a deep social orientation. It is shown that he attached great importance to the problems of poverty, social stratification, illiteracy, drunkenness, backward healthcare, a raw materials economy, and the contradictions of capitalism. It is emphasized that the publicist paid attention to the problem of human loneliness in society in the context of the implementation of new technical inventions (aviation, railways, telephone, etc.), reflected on the idea of increasing alienation between the people and the authorities. The author of the article points to the value and fairness of M. O. Menshikov’s judgments about the importance of considering the press as the most important institution of civil society, as well as the need to form a powerful middle class as the basis of civil society. The biography of M. O. Menshikov is considered, its place in the history of domestic conservatism is characterized.